2015
DOI: 10.5812/jjm.19766v2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of HIV/AIDS in the East Azerbaijan Province, Northwest of Iran

Abstract: Background:This study was performed in response to the rapid propagation of HIV/AIDS across Iran and its status in this region. Accordingly, an evidence-based program is required to combat this disease.Objectives:The present study estimated the prevalence of HIV/AIDS in East Azerbaijan (population: 3,724,000).Materials and Methods:We created a database of all positive cases from 1987 to 2012. We also analyzed and described the epidemiological status of HIV/AIDS during a 25-year period by using SPSS.Results:In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
5
0
3
Order By: Relevance
“…Esto va respaldado con los resultados de otros estudios que hallaron un predominio de varones del 66,7 %, 80,0 % y 91 % de pacientes infectados con VIH. [5][6][7] En lo que respecta a progresión a estadio sida, algunos hallaron que el sexo masculino se asoció significativamente a un diagnóstico tardío y estadio avanzado de infección por VIH. 8,9 Esto es contrario a otro estudio que identificó al sexo femenino como factor asociado a progresión rápida a sida.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Esto va respaldado con los resultados de otros estudios que hallaron un predominio de varones del 66,7 %, 80,0 % y 91 % de pacientes infectados con VIH. [5][6][7] En lo que respecta a progresión a estadio sida, algunos hallaron que el sexo masculino se asoció significativamente a un diagnóstico tardío y estadio avanzado de infección por VIH. 8,9 Esto es contrario a otro estudio que identificó al sexo femenino como factor asociado a progresión rápida a sida.…”
Section: Resultsunclassified
“…8 Estos resultados difieren de los dados según el Análisis de la Situación Epidemiológica en el Perú, 4 que en el último quinquenio (2014-2018) observó un incremento en los casos de infección de VIH en el grupo de 20 a 29 años (población joven). [5][6][7] Con respecto al estado civil, 49,48 % (n = 241) de infectados con VIH eran solteros, similar a otro estudio que encontró 58,59 % de solteros en los infectados con VIH. En contraste, otro estudio halló que 54,2 % de oficiales infectados con VIH eran casados.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…In two different studies on female sex workers, the prevalence of HSV2 was reported as 9.7% and 18% (26,30). HIV/AIDS: Although the condition of HIV epidemic is concentrated in Iran, its prevalence in the general population is extremely low (11,12,19,(28)(29)(30)(31)(32)(33). The condition of Epidemic concentration is covering injecting drug users with prevalence of 12.3%-26.6% in Tehran and 18.8%-15.2% throughout the country (34-36).…”
Section: Prevalence Of Stis In Iranmentioning
confidence: 99%
“…BMI is considered to be the foremost index in epidemiological studies due to the easiness of its measurement [6][7][8]. By definition, BMI of 25-29.9 kg/m 2 is referred to as overweight, and amounts of over 30 kg/m 2 represent obesity [9].…”
Section: Introductionmentioning
confidence: 99%